MODEST FASHION ITANG YUNASZ DALAM FOTOGRAFI KOMERSIAL - Dhimo Kukuh Priyambodo (Institut Seni Indonesia Yogyakarta, 2020)
The creation of the photographic work modest fashion Itang Yunasz in commercial photography will discuss how modest fashion Itang Yunasz is displayed in a visual that attracts consumers by highlighting the characteristics of clothing according to the target market. The object in the creation of this photographic work is a fashion label that is under the auspices of Itang Yunasz namely